A large case series of temporal bone fractures at a UK major trauma centre with an evidence-based management protocol. Issue 3 (3rd March 2020) - Kanona, H; Anderson, C; Lambert, A; Al-Abdulwahed, R; O'Byrne, L; Vakharia, N; Motter, D; Offiah, C; Adams, A; Seymour, K; Wareing, M J
Abstract: Objective: To review the management of temporal bone fractures at a major trauma centre and introduce an evidence-based protocol. Methods: A review of reports of head computed tomography performed for trauma from January 2012 to July 2018 was conducted. Recorded data fields included: mode of trauma, patient age, associated intracranial injury, mortality, temporal bone fracture pattern, symptoms and intervention. Results: Of 815 temporal bone fracture cases, records for 165 patients met the inclusion criteria; detailed analysis was performed on the records of these patients. Conclusion: Temporal bone fractures represent high-energy trauma. Initial management focuses on stabilisation of the patient and treatment of associated intracranial injury. Acute ENT intervention is directed towards the management of facial palsy and cerebrospinal fluid leak, and often requires multidisciplinary team input. The role of nerve conduction assessment for immediate facial palsy is variable across the UK. The administration of high-dose steroids in patients with temporal bone fracture and intracranial injury is not advised. A robust evidence-based approach is introduced for the management of significant ENT complications associated with temporal bone fractures.